A Brief History of the College of The Bahamas’ Athletics Department. - Rolle, Kimberley (International Journal of Bahamian Studies, 2015)
The College of The Bahamas Athletics Department encompasses intercollegiate athletics, health and wellness, and recreational intramural sports. COB’s Wellness Centre provides fitness equipment, health and wellness counseling, and group exercise classes for students, faculty and staff. The College’s soccer, basketball, and track and field teams compete internationally with schools in Florida and the Caribbean. The Athletics Department works consistently to increase international opportunities for COB student athletes to excel abroad.